History and Urgency of Indonesian in Konoha - Adhani, Indah; Hasibuan, Putri Chairany; Aprina, Syalsa Dwi (Jurnal Riset Ilmu Pendidikan, 2023)
This study was designed to uncover the origins of the name "Konoha" for Indonesia as well as the significance of the Indonesian language in the Unitary State of the Republic of Indonesia (NKRI). In this study, we use a literature-based strategy by examining a variety of sources that are virtually exclusively written works. In the Federal Republic of Indonesia (NKRI), Indonesian is spoken as the official language. The Indonesian language has to be able to become the primary form of communication for the Indonesian people in order to keep up with the increasing pace of globalization, modernity, science, and technology. On October 28, 1928, in Jakarta, young Indonesians took the Youth Pledge, marking the beginning of efforts to establish Indonesian as the country's official language